Microbiological quality of foods served during Malay wedding banquets, and relationship with food safety knowledge of food handlers - Ahmad, Nor Aisyah (2018)
Food poisoning is a critical problem to public health, and is increasingly reported in Malaysia. One of the major causes for food poisoning is wedding banquets. Foodborne outbreak related to wedding banquet was reported on September 30th, 2013 which caused three deaths, two in critical condition and about sixty hospitalizations after attending a wedding banquet at Sungai Petani, Kedah. Compiling and analysing the data on food poisoning cases from wedding banquets and their root causes is thus important in providing the general idea on the safety status of foods being served. The aim of the present work was therefore to identify the relationship between microbiological quality of the foods served during a wedding banquet and the temperature control awareness among its food handlers. The two selected Malay wedding banquets were each prepared by commercial catering services and ‘rewang’ activity (a group of voluntary cook from the local community) in Selangor. Three types of dish (chicken, vegetable and cooked rice) were sampled from both banquets and analysed for Total Plate Count (TPC), Total Coliform, Escherichia coli, Staphylococcus aureus, Bacillus cereus, Salmonella, and Listeria monocytogenes. The dishes that have been taken are chicken curry, pajeri nanas and cooked white rice. The dish samples were taken at 0, 1, 2, 3 and 4 h after serving. The drink sample was analysed for Total Coliform and E. coli. The utensils used during the wedding banquet were analysed for TPC. A food safety knowledge questionnaire was completed by selected food handlers by using face to face interview. The questionnaire was performed to know the understanding of the food handlers and also their operational behaviour and personal routine. The results reveal that at 0 h the microbial load was already high for both catering and rewang. For catering, the TPC for chicken, vegetable and cooked rice at 0 h were 6.39, 6.21 and 7.13 log10 CFU/g respectively. For rewang, the TPC for chicken, vegetable and cooked rice at 0 h were 6.54, 6.13 and 7.63 log10 CFU/g respectively. None of the samples were contaminated with Salmonella sp. or Listeria sp. Total Coliform obtained from catering for drink was 4.40 log10 CFU/mL and for rewang was 3.10 log10 CFU/mL. The temperature of foods during the serving times averaged between 30°C-50°C which were conducive for bacterial proliferation. The questionnaire respondents from the catering services mostly have attended food safety seminar whereas respondents from the rewang never attended any food handling training. The result shows that 26.7% attended the training whereas 73.3% did not attend any food handling training. However, both categories appeared unconcerned about temperature control during food preparation and serving. About 93.3% respondent do not monitor food temperature during cooking process. This could relate to the high microbial contamination observed. Even though the selected food handlers have attended food safety training but their awareness toward the importance of temperature control was still lacking.